2022
DOI: 10.1038/s42003-022-04097-y
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of mTORC1-dependent activation of the ubiquitin-proteasome system in muscle proteostasis

Abstract: Muscle size is controlled by the PI3K-PKB/Akt-mTORC1-FoxO pathway, which integrates signals from growth factors, energy and amino acids to activate protein synthesis and inhibit protein breakdown. While mTORC1 activity is necessary for PKB/Akt-induced muscle hypertrophy, its constant activation alone induces muscle atrophy. Here we show that this paradox is based on mTORC1 activity promoting protein breakdown through the ubiquitin-proteasome system (UPS) by simultaneously inducing ubiquitin E3 ligase expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…7E), which were all downregulated in AktTG mice and upregulated in HSA-MycTG mice. Although the expression of ribosomal protein genes was suppressed in AktTG mice, translation of these genes is potently upregulated by PKB/Akt-mTORC1 pathway activity, resulting in higher ribosomal protein abundance [37]. Hence, despite the strong overlap of gene regulatory networks associated with cell growth, as previously observed [8], the resulting effect of Myc expression on post-mitotic muscle fibers is catastrophic, whereas PKBα/Akt1 activation results in functional hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7E), which were all downregulated in AktTG mice and upregulated in HSA-MycTG mice. Although the expression of ribosomal protein genes was suppressed in AktTG mice, translation of these genes is potently upregulated by PKB/Akt-mTORC1 pathway activity, resulting in higher ribosomal protein abundance [37]. Hence, despite the strong overlap of gene regulatory networks associated with cell growth, as previously observed [8], the resulting effect of Myc expression on post-mitotic muscle fibers is catastrophic, whereas PKBα/Akt1 activation results in functional hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
“…In these mice, the PKBα/Akt1-ERT fusion protein is constitutively expressed in skeletal muscle fibers but immediately degraded and hence not active. Injection of tamoxifen, which binds ERT, stabilizes the PKBα/Akt1-ERT fusion protein, rendering it constitutively active [38, 39] and causing robust PKBα/Akt1-mediated muscle hypertrophy [37]. Just 3 days of tamoxifen injections was sufficient to promote measurable increases in QUAD, EDL, PLA, GAS and TRI muscle mass in female mice, while 14 days of tamoxifen treatment robustly increased the mass (25-75%) of all measured muscles, except the slow-twitch SOL muscle, which displayed just a minor ∼6% increase in mass (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, loss of Nfe2l1 did not completely abolish proteasomal activity, which indicates that the baseline of proteasome subunit gene expression is likely mediated by a different, less adaptive mechanism, which could be mediated by e.g., FoxO1 27 . Nfe2l1 is also linked to mTORC1 signaling, as sustained genetic activation of mTORC1 promotes Nfe2l1 activation, proteasomal activity, and muscle atrophy 28 . However, this study also demonstrated juxtaposed roles of the UPS in atrophy and proteome integrity, which is in line with our findings that loss of Nfe2l1 creates a lean phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to increase the proteolytic capacity of cells and treat human diseases caused by protein misfolding might include increasing the total proteasome pool. Several studies in diverse experimental systems, including mouse fibroblasts, the brain, the retina, and muscles, reported higher levels of proteasomes under genetic activation of the mTORC1 (mechanistic target of rapamycin complex 1) pathway (22)(23)(24)(25)(26). The mechanisms driving this transcriptional program have not been fully characterized but are proposed to be triggered by sterol-regulatory element binding protein 1 (Srebp1)-mediated transcriptional upregulation of the nuclear factor erythroid-2-like 1 (Nfe2l1) transcription factor (22,27).…”
Section: Introductionmentioning
confidence: 99%